Analisis Prioritas Pengembangan Kawasan Wisata Alam Pantai di Kabupaten Tanah Bumbu - Seftiani Seftiani; Ika Chandriyanti (PPJP Universitas Lambung Mangkurat, 2023)
This study aims to determine what criteria are the most dominant in determining the priority criteria for developing coastal natural tourism areas in Tanah Bumbu Regency and to find out what alternative options show the most dominant results so that these alternatives become the priority focus of developing coastal natural tourism areas in Tanah Bumbu Regency. The data analysis technique used is the Analytical Hierarchy Process (AHP) method, namely determining policy priorities for the development of coastal tourism in Tanah Bumbu Regency.The results of this study indicate that among the criteria for access, facilities, and attractiveness, the most dominant criterion to be determined as a priority criterion in coastal natural tourism areas in Tanah Bumbu Regency is the attractiveness criteria with a preference value of 68% then the facility criteria are with a preference value of 20%, and the last is access with a preference value of 12%. And of the 2 (two) alternatives that are used as research objects, the Pagatan Beach alternative has the highest preference value with a value of 63% and the second is the Angsana Beach alternative with a preference value of 37%.